Studying Customer Behavior in the Libyan Telecoms Market using Data Visualization - Aya Taher Sherif; Saber Khaled Elmabrouk (Journal of Pure & Applied Sciences, 2023)
In general, the main benefit of data visualization is that it provides a better understanding of complex data and enables faster decision-making.This study on call detail records (CDRs) and SMS activity data visualization was conducted to fully understand the customer behavior patterns and culture in the Libyan telecom market.A big telecom data (261 GB) was collected for CDRs between 28 March and 22 April 2020. This includes 19 working days, three Fridays and four Saturdays. The data visualization results show that the weekend SMS and call activity pattern shows a completely different behavior compared to other days of the week. Call behavior between 12:00 and 7:00 is generally almost the same. The peak times for calls on weekdays are between 11:30 and 13:00 and for SMS between 19:30 and 22:00. Furthermore, the analysis of SMS activities does not reflect customer behavior, but much of the SMS activity is the result of electronic payment services during shopping. However, Libyan culture is more about making phone calls than sending SMS messages. since the number of calls at dawn is minimal, the number of SMS increased slightly at this time. In order to retain customers, decision makers should consider these results and develop appropriate plans and strategies. However, in order to reduce call congestion and increase efficiency, decision makers should set appropriate pricing during peak or pre-peak and post-peak hours to convert many customers before or after peak hours.Also, they should somehow encourage customers to use SMS instead of calls.